Safeguards Assessments : 2011 Update. (Policy Papers; Policy Paper, 2011)
Under the Fund's safeguards policy introduced in 2000, assessments of central banks are carried out for countries seeking financing from the IMF. They are part of the Fund's approach to prudent lending and complement the Fund's other safeguards such as program design, conditionality, and access limits, to name a few. The assessments aim to provide reasonable assurance that governance and controls can protect Fund resources from misuse and guard against misreporting of monetary data used for program monitoring purposes.